Efficacy of high-vision transnasal endoscopy using texture and colour enhancement imaging and narrow-band imaging to evaluate gastritis: a randomized controlled trial. (31st December 2022) - Sugimoto, Mitsushige; Kawai, Yusuke; Morino, Yuko; Hamada, Mariko; Iwata, Eri; Niikura, Ryota; Nagata, Naoyoshi; Koyama, Yohei; Fukuzawa, Masakatsu; Itoi, Takao; Kawai, Takashi
Abstract: Background: A new image-enhanced endoscopy method called texture and colour enhancement imaging (TXI) enhances brightness, surface irregularities, and subtle colour changes in endoscopic images. However, it is unclear whether TXI and narrow-band imaging (NBI) with third-generation high-vision transnasal ultrathin endoscopy are advantageous over white-light imaging (WLI) for detecting atrophy, intestinal metaplasia, map-like redness and gastric cancer. We investigated to compare the endoscopic efficacy for evaluation of gastritis between TXI and NBI with high-vision transnasal endoscopy and clarified the endoscopic efficacy of TXI and NBI compared to WLI. Methods: We enrolled 60 patients who underwent high-vision transnasal endoscopy as part of a health check-up from March to November 2021 and randomized patients into two groups (the WLI-NBI group and the WLI-TXI group) using the minimization method based on Helicobacter pylori infection status, age and sex. Colour differences determined using the International Commission on Illumination 1976 (L∗, a∗, b∗) colour space was compared between WLI and TXI or NBI. Results: No significant differences were observed in colour differences surrounding atrophy, intestinal metaplasia and map-like redness between NBI and TXI ( p  = .553, .057 and .703, respectively). Endoscopic scores based on the Kyoto classification of gastritis for atrophy, intestinal metaplasia, and map-like redness were similar between WLI and TXI. In contrast, NBI identified intestinal metaplasia at a significantly greater rate than WLI ( p  = .018). Further, colour differences surrounding atrophy and intestinal metaplasia on TXI and NBI were significantly greater than those on WLI (atrophy: TXI vs WLI p  = .003, NBI vs WLI p  < .001; intestinal metaplasia: TXI vs WLI p  = .016, NBI vs WLI p  < .001). However, TXI and NBI were not advantageous over WLI for detecting map-like redness. Conclusion: Third-generation high-vision transnasal ultrathin endoscopy using TXI and/or NBI is useful for detecting atrophic borders and intestinal metaplasia. Key Messages: High-vision transnasal endoscopy using TXI or NBI is useful for diagnosing and detecting atrophy and intestinal metaplasia. TXI and NBI increase colour differences surrounding atrophy and intestinal metaplasia, thereby increasing diagnostic efficiency to improve risk stratification for gastric cancer. The image quality and detection rate have improved markedly with the latest ultrathin high-vision transnasal endoscopes.